Legal Certainty to Protect Sport Industry Company Related to Technological Doping Among Athletes in Athletics - Mohammad Choirul Anam; Pujiyono Pujiyono (International Journal Labs, 2023)
This study aims to analyze the legal problems of the phenomenon of technological doping in athletic sports, legal certainty for the protection of sports industry companies related to the phenomenon of technological doping among athletes in athletic sports, and the impact of world athletics policies on patent enforcement. The author uses normative legal research methods with a statutory approach and a conceptual approach that is analyzed qualitatively with descriptive methods sourced from primary, secondary, and tertiary legal materials. The results of the study indicate that the legal problem of the phenomenon of technological doping in athletic sports is that there is no legal certainty regarding the characteristics of the elements of the use of sports equipment technology which is considered to provide unfair advantages for athletes in competition. So that regulations are needed that can explain how technology is considered to be able to provide unfair advantages in competition. Legal certainty for the protection of sports industry companies related to the phenomenon of technological doping among athletes in the field of athletics is through the examination of sports equipment by independent experts, the availability of products in general sales, the suitability of shoe soles based on a predetermined thickness, and sanctions against athletes and delegation members. However, the policies in World Athletics may result in the reduction of exclusive rights owned by inventors to products that have obtained patents. So that to obtain maximum benefits in patent registration for athletic sports products, it is necessary to consider several things including the originality of the invention against other products, the potential harm caused, and consideration of the time between patent filing and sales to the open market.